Logic Gates and Ring Oscillators Based on Ambipolar Nanocrystalline-Silicon TFTs - Anand Subramaniam; Kurtis D. Cantley; Eric M. Vogel (Active and Passive Electronic Components)
Nanocrystalline silicon (nc-Si) thin film transistors (TFTs) are well suited for circuit applications that require moderate device performance and low-temperature CMOS-compatible processing below 250°C. Basic logic gate circuits fabricated using ambipolar nc-Si TFTs alone are presented and shown to operate with correct outputs at frequencies of up to 100 kHz. Ring oscillators consisting of nc-Si TFT-based inverters are also shown to operate at above 20 kHz with a supply voltage of 5 V, corresponding to a propagation delay of <10 μs/stage. These are the fastest circuits formed out of nanocrystalline silicon TFTs to date. The effect of bias stress degradation of TFTs on oscillation frequency is also explored, and relatively stable operation is shown with supply voltages >5 V for several hours.